Effectiveness of Cascade Aerator Overflow System in Reducing Fe Levels in Excavated Well Water - Ramadhani, Hani; As, Zulfikar Ali As; Pahruddin, Muhammad; Junaidi (Gema Lingkungan Kesehatan, 2025)
Water is an essential resource that profoundly influences the quality of human life. In Indonesia, approximately 73.03% of the population continues to depend on water sourced from protected dug wells for their daily needs. This is particularly evident in Tambak Baru Ilir Village, located in Banjar Regency, South Kalimantan, where residents rely on dug well water as their primary source of potable water. However, the concentration of iron (Fe) in this water source often exceeds the acceptable threshold for drinking water quality, which is set at 0.2 mg/L, presenting a significant public health concern in the region. The objective of this study is to assess the efficacy of the Cascade Aerator overflow system in mitigating Fe levels in dug well water. The research employed a purely experimental design utilizing a Pretest-Posttest Control Group framework, incorporating seven variations of aeration contact time ranging from 0 to 60 minutes. Measurements of Fe concentration, pH, and temperature were conducted, and the data were subjected to linear regression analysis. The findings revealed a substantial reduction in Fe levels, decreasing from 1.125 mg/L to 0.385 mg/L at a 60-minute contact duration, which corresponds to an efficiency reduction of 63%. Concurrently, the pH value increased from 6.3 to 7.8, and the temperature remained within acceptable limits. Regression analysis indicated a strong correlation between contact time and the reduction of Fe levels, with an R² value of 93.4%. Although the final Fe concentration did not meet established quality standards, the Cascade Aerator system demonstrates potential as a viable technology for the treatment of well water. Further advancements, such as the integration of filtration units or extending the contact time beyond 75 minutes, are recommended to enhance the effectiveness of this treatment method.